2012
DOI: 10.1292/jvms.11-0354
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Ovarian Cysts Originating from Rete Ovarii in an African Green Monkey (<i>Cercopithecus Aethiops</i>)

Abstract: ABSTRACT. Ovarian cyst is common incidental finding in humans and many animals and includes follicular cysts, cystic rete ovarii and mesonephric duct cysts. Ovarian cyst is often associated with reproductive disorders in humans and animals. We found accidentally bilateral cystic masses in ovaries in an African green monkey. Grossly, the left and right ovarian cystic masses were single unilocular cystic structures measuring 0.6 and 1.8 cm in diameter, respectively. Histologically, both cysts were thin-walled st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The choice of surgical methods is mainly determined by the location of the cyst and the specific conditions during the operation. Cystectomy was performed clinically for oviducts, ovarian crowns, broad ligaments, and retroperitoneal mesonephric cysts [9]. Cystectomy or hysterectomy may be performed according to the size and location of the cyst in the renal duct of the uterus [10].…”
Section: Case Reportmentioning
confidence: 99%
“…The choice of surgical methods is mainly determined by the location of the cyst and the specific conditions during the operation. Cystectomy was performed clinically for oviducts, ovarian crowns, broad ligaments, and retroperitoneal mesonephric cysts [9]. Cystectomy or hysterectomy may be performed according to the size and location of the cyst in the renal duct of the uterus [10].…”
Section: Case Reportmentioning
confidence: 99%
“…The Rete Ovarii (RO) is an epithelial structure that is directly connected to the ovary, first described over a century ago (Waldeyer, 1870) as a multi-region structure of mesonephric origin. Despite high conservation among mammalian species including guinea pigs, cows, cats, sheep, swine, prairie deer mice, camels, dogs, monkeys (Cassali et al, 2000;Kim et al, 2012), cows (Santos et al, 2012), and humans (Khan et al, 1999), previous work on the RO did not arrive at a consensus on the function of this structure. Thus, it has remained a mysterious orphan structure.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the cyst is identical between cystic rete ovarii and cystic rete testis in rabbits. However, as it has been demonstrated in the normal ovarian tissue and neoplastic rete ovarii of humans, the epithelial cells of the female counterpart in rabbits expressed estrogen receptor [12, 17]. Though reports on calretinin expression in rete ovarii and rete testis are very limited, Cao et al reported that 0/2 cases of rete ovaries were calretinin-positive, and 2/8 cases of rete testes were calretinin-positive in humans [5].…”
mentioning
confidence: 99%